Pathogenic and molecular variation among Indian isolates of Tilletia indica causing Karnal bunt of wheat - RATAN TIWARI; S. NAGARAJAN, J. KUMAR*, M.S. SAHARAN, A.K. SHARMA, SUDHIR SHARMA, SOMVIR (Indian Phytopathology, 2004)
Eight hundred and fifty eight isolates of Tilletia indica collected from north west plain zone (NWPZ) of India over a span of three crop seasons when evaluated by Polyacrylamide Gel Electrophoresis (PAGE) test revealed the presence of three protein types. The PAGE test perfectly demarcated the three protein variants and by doing RAPD profiling of these three protein variants, the isolates of T. indica could be characterized precisely. Populations of these variants determined with the help of PAGE and RAPD analyses were restricted to three agro climatic zones within NWPZ and showed differential pathogenicity on a set of wheat genotypes. This information may assist in efficient breeding for Karnal bunt resistance by identifying resistant sources against area specific isolates of Tilletia indica.